Prevalence of herbicide-resistant weed species in Malaysian rice fields: A review - Ruzmi, Rabiatuladawiyah; Ahmad Hamdani, Muhammad Saiful; Bakar, Baki (John Wiley & Sons, 2017)
The management of weeds in Malaysian rice fields is very much herbicide-based. The heavy reliance on herbicide for weed control by many rice-growers arguably eventually has led to the development and evolution of herbicide-resistant biotypes in Malaysian rice fields over the years. The continuous use of synthetic auxin (phenoxy group) herbicides and acetohydroxyacid synthase-inhibiting herbicides to control rice weeds was consequential in leading to the emergence and prevalence of resistant weed biotypes. This review discusses the history and confirmed cases and incidence of herbicide-resistant weeds in Malaysian rice fields. It also reviews the Clearfield Production System and its impact on the evolution of herbicide resistance among rice weed species and biotypes. This review also emphasizes the strategies and management options for herbicide-resistant rice field weeds within the framework of herbicide-based integrated weed management. These include the use of optimum tillage practices, certified clean seeds, increased crop competition through high seeding rates, crop rotation, the application of multiple modes of action of herbicides in annual rotations, tank mixtures and sequential applications to enable a broad spectrum of weed control, increase the selective control of noxious weed species in a field and help to delay the resistance evolution by reducing the selection pressure that is forced on those weed populations by a specific herbicidal mode of action.